The Role of Islamic Education at Syafa'atut Thulab Islamic Boarding School's Senior High School in Improving Citizenship and Social Awareness in Indonesia's Multicultural Society - M. Qusyairi Abror; Siti Marfuah; Virdatus Sholikhah; Supriyadi Supriyadi; Hilmin Hilmin (West Science Social and Humanities Studies, 2026)
This study aims to analyze the role of Islamic education at Madrasah Aliyah Pondok Pesantren Syafa’atut Thulab in enhancing students’ sense of citizenship and social awareness within Indonesia’s multicultural society. The research is grounded in the belief that Islamic education serves not only as a medium for religious formation but also as a means of developing national and social character. This study employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings reveal that the implementation of Islamic education at the madrasah integrates both the national and religious curricula, supported by daily habituation of akhlaq al-karimah (noble character) among students. Islamic education significantly contributes to shaping students’ civic awareness, such as patriotism, responsibility, and concern for the surrounding community. Moreover, social activities such as community service, environmental cleanups, and outreach programs strengthen students’ social character. The main supporting factors include the religious environment of the pesantren, teachers’ exemplary attitudes, and the madrasah’s integrated programs, while the inhibiting factors include limited facilities and external cultural influences. This research concludes that Islamic education plays a vital role in cultivating a generation that is religiously devout, nationally conscious, and socially responsible.